Temperature field characteristics of slab ends of double-block ballastless track in large daily temperature difference region - Youxin Wei; Yu Liu; Bin Yang; Shiping Zhang; Yanxi Zhao (Case Studies in Thermal Engineering)
In regions with large daily temperature differences, double-block ballastless tracks have experienced severe interface damage and warping deformation at the slab ends. A new indoor experiment was conducted on the track structure, simulating temperature variations through controlled air temperatures. Cross-sectional infrared data was analyzed to explore overlooked temperature field characteristics of slab ends. Combined with numerical simulations, the temperature field of the track slab was further analyzed. The results show that the daily temperature difference within the slab interior is significantly less than 50 % of that in the ambient air, whereas the daily temperature difference within a 60 cm range at the slab ends is much higher. Notably, the outermost 30 cm of the slab ends experiences a daily temperature difference that is 6–7 °C greater than that within the slab interior. The temperature gradient distribution at the slab ends displays a complex pattern, deviating from the typical top-to-bottom decreasing trend. Moreover, the maximum vertical overall temperature gradient across the track slab reaches approximately 30 °C/m. To enhance the adaptability of double-block ballastless tracks to harsh temperature environments, optimization of expansion joint settings and adjustment of design value for negative temperature gradient are recommended.